Algocracia: Uma análise crítica sobre a gestão mediada por algoritmos - Neves, Ianaira Barretto Souza (2022)
The purpose of this essay was to reflect on the use of algorithms by organizations, especially in the mediation of work management, that has resulted in a model named algocracy. This system is guided by the search for efficiency and legitimized by the new information and communication technologies, affecting work relationships, organizational structures, and cultural, economic, social, and political aspects. For such reflection, we observed this algorithmic management model through the lens of critical management studies. We argue that the neoliberal context camouflages disparities between organizations and workers by legitimizing the ideology of flexibility and using algorithms to capture data, process it, and decide on workers' activities and assessments.